Analisis Pengaruh Frekuensi Belajar di Luar Sekolah dan Motivasi Belajar terhadap Hasil Belajar IPA: The Effect of Frequency of Out-School Learning Activities and Learning Motivation on Student's Science Learning Outcomes - Hartina, Tika; Mahrus, Mahrus; Hadiprayitno, Gito (SEJ (Science Education Journal), 2019)
The purpose of this study is to determine the effect of frequency of out-school learning activities and learning motivation towards improving students' natural science learning achievement. This research is quantitative research with an ex-post facto approach. The subjects in the study were 8th grade students of SMP Negeri 8 Mataram in the academic year at 2018/2019 with a total of 260 people. Data collection of science learning outcomes is obtained from daily tests from teachers in schools while data collection of the frequency of out-school learning activities and learning motivation is obtained using a questionary. The effect of frequency of out-school learning activities and learning motivation on learning achievement of science are analyzed using analysis of covariance (ANAKOVA). The results of the study show that: 1) the frequency of out-school learningactivities has a significant influence on science learning achievement; 2) student's learning motivation has a significant effect on science learning achievement, and 3) there is an interaction between the frequency of out-school learning activities and learning motivation on students' learning achievement in science. The frequency of out-school learning activities and learning motivation is proven have effect on science learning achievement.